Competition and artistic gymnastics: How to make the most of this experience - Nunomura, M.; Okade, Y.; Tsukamoto, M. H. C. (International Journal of Sport & Health Science, 2009)
Sport participation has been growing worldwide and its potential benefits are well known. However, youth competitive sport is still a matter of debate. Competition is inherent to sport, but discussions abound when young athletes are involved. This is particularly the case in sports where early specialization and high training loads are the norm, such as artistic gymnastics. In the present study we interviewed 46 coaches, who are coaching developing elite gymnasts in Brazil, and attempted to understand their attitudes toward competition. Coaches expressed concern about the motivation, the ability of athletes to set their own goals, and providing extrinsic rewards. In contrast, some coaches saw extrinsic rewards as an effective strategy to keep their athletes committed. The study highlighted the need for both concern and understanding by coaches about individual differences due to maturation and growth.